A family of diastereomeric dodecanuclear coordination cages based on inversion of chirality of individual triangular cyclic helicate faces. Issue 37 (11th September 2020) - Argent, Stephen P.; Jackson, Fiona C.; Chan, Ho Man; Meyrick, Sam; Taylor, Christopher G. P.; Ronson, Tanya K.; Rourke, Jonathan P.; Ward, Michael D.
Abstract : All three diastereoisomers of a cuboctahedral coordination cage containing square and triangular faces, based on different chirality of each triangular face independently, have been structurally characterised. Abstract : The dodecanuclear coordination cage [Cd12 (L naph )12 (L mes )4 ](BF4 )24 consists of a set of four triangular, trinuclear helical panels {Cd3 (μ-L naph )3 } 6+ (based on ditopic bridging ligands L naph ), which are connected by four tritopic ligands L mes . The result is that the four triangular helical panels and the four L mes -capped triangular faces of the cuboctahedral core form two alternating subsets of the eight triangular faces of the cuboctahedron. Crystallographic investigations revealed that the triangular helicate faces can have 'clockwise' (C) or 'anticlockwise' (A) helicity, and that the helicity of each face can vary independently of the others as they are mechanically separated. This generates a set of three diastereoisomers in which all four cyclic helicate faces in the cuboctahedron have the same chirality (AAAA/CCCC enantiomers with T symmetry; AAAC/CCCA enantiomers with C 3 symmetry; and achiral AACC with S 4 symmetry). This mirrors the known behaviour of many simpler M4 L6 tetrahedral cages which can likewise exist as T, C 3 or S 4 isomers according to the sense of tris-chelate chirality around each individual metal centre: but here it is translated onto a much larger scale by the four chiral units being entire trinuclear helicate faces rather than single metal centres. 1 H NMR spectroscopy confirms the presence of the three diastereoisomers with their different molecular symmetries in a ratio slightly different from what is expected on purely statistical grounds; and 1 H NMR measurements on a non-equilibrium sample (enriched by manual crystal-picking before preparing the solution) showed that the distribution does not change over several weeks in solution, indicating the kinetic inertness of the cage assemblies.